The Fourth International Conference on Heterogeneous Networking for Quality, Reliability, Security and Robustness &Amp; Worksho 2007
DOI: 10.1145/1577222.1577285
|View full text |Cite
|
Sign up to set email alerts
|

Where EAP security claims fail

Abstract: The Extensible Authentication Protocol (EAP) is widely used as an authentication framework to control the access to wireless networks, e.g. in IEEE 802.11 and IEEE 802.16 networks. In this paper, we discuss limitations of EAP security and demonstrate how these limitations can be exploited to launch attacks on existing EAP methods. In particular, we present a series of attacks which cause some standard security claims, namely channel binding, protected ciphersuite negotiation and cryptobinding, to fail and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Checking the consistency of i1 and i2 is nontrivial, as has been pointed out already in [HC07]. First, i1 can contain any type of information propagated by the authenticator, whereas i2 is restricted to information that can be carried in AAA attributes.…”
Section: Channel-binding Consistency Checkmentioning
confidence: 99%
“…Checking the consistency of i1 and i2 is nontrivial, as has been pointed out already in [HC07]. First, i1 can contain any type of information propagated by the authenticator, whereas i2 is restricted to information that can be carried in AAA attributes.…”
Section: Channel-binding Consistency Checkmentioning
confidence: 99%
“…However, they require the interaction between the foreign server and the home server, which may lead to the single point of failure [34], and induce large authentication transmission overhead because of the long distance between the foreign server and the home server. Moreover, recent studies [35], [36] have shown that SC-based schemes cannot provide strong user anonymity and non-traceability, and most of them cannot provide session key security and resistance to sophisticated attacks. Another weakness is that, they cannot flexibly be applied to all application scenarios because each protocol is only suitable for the corresponding network architecture, this may increase the complexity of the entire system.…”
Section: Related Workmentioning
confidence: 99%
“…MitM attacks on tunneled authentications and authentications in anonymous tunnels have been identified in [3] and [8], respectively. For the sake of simplicity, we review the attacks for scenarios in which tunnel server and inner authentication server are the same entity.…”
Section: B Previous Workmentioning
confidence: 99%
“…As an alternative to cryptographic bindings, the authors in [3] suggest enforcing a policy that prevents authentication methods that are tunneled from being executed outside a protective tunnel. Similarly, the authors in [8] propose a number of security policies, including to prohibit anonymous tunnels, to thwart the reviewed attacks.…”
Section: ) Upon a Successful Authentication The Master Session Keymentioning
confidence: 99%
See 1 more Smart Citation